2023
DOI: 10.1007/s00381-023-06062-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective dorsal rhizotomy in non-ambulant children with cerebral palsy: a multi-center prospective study

Abstract: Purpose Assess the effects of selective dorsal rhizotomy (SDR) on motor function and quality of life in children with a Gross Motor Function Classification System (GMFCS) level of IV or V (non-ambulatory). Methods This is a prospective, observational study in three tertiary neurosurgery units in England, UK, performing SDR on children aged 3–18 with spastic diplegic cerebral palsy, and a GMFCS level of IV or V, between 2012 and 2019. The primary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, it was concluded that aggressive spasticity treatment by SDR does not result in significant differences in gait kinematics in individuals with cerebral palsy in young adulthood compared to minimal spasticity treatment ( 2 ). However, the results of SDR may differ between ambulatory and nonambulatory patients ( 3 ). It is also conceivable that unsupervised machine learning methods can effectively and accurately classify patients into different subgroups suffering from cerebral palsy based on preoperative characteristics, and improve outcome after SDR through better selection ( 4 ).…”
mentioning
confidence: 99%
“…Therefore, it was concluded that aggressive spasticity treatment by SDR does not result in significant differences in gait kinematics in individuals with cerebral palsy in young adulthood compared to minimal spasticity treatment ( 2 ). However, the results of SDR may differ between ambulatory and nonambulatory patients ( 3 ). It is also conceivable that unsupervised machine learning methods can effectively and accurately classify patients into different subgroups suffering from cerebral palsy based on preoperative characteristics, and improve outcome after SDR through better selection ( 4 ).…”
mentioning
confidence: 99%